ANALYSIS OF FACTORS INFLUENCING TEACHERS’ INSTRUCTIONAL PRACTICES AND INNOVATION IN KAZAKHSTAN: EVIDENCE FROM TALIS 2018 - Kulmagambetova, Axlu (Nazarbayev University Graduate School of Education, 2022)
Teachers' instructional and professional practices can help students improve in school, and team innovation can help teachers improve their teaching. Based on the TALIS 2018 (Teaching and Learning International Survey) data, this study examines teachers' instructional approaches such as classroom management, clarity of instruction, cognitive activation, self-efficacy in teaching, and professional development in various Kazakhstani schools. Using confirmatory factor analysis and structural equation modelling, this study explores the links between instructional practice and innovation in Kazakhstan. Findings reveal that, in Kazakhstan, there exist few systematic disparities in teachers' preparation in classroom management and instructional practice between schools. Analysis reveals that instructional practice elements, such as self-efficacy in student engagement, clarity of instruction, and the need for professional development in subject matter and pedagogy, are major predictors of team innovativeness among teaching practitioners. In addition, the age group (maturity) and gender (being male) also contribute positively to the level of Kazakhstani team innovativeness among teachers in Kazakhstan. The research adds findings to a better understanding of the components that affect teachers' instructional and innovative practices in Kazakhstan and proposes approaches to improve educators' pedagogical and professional practices. Implications for policy and practice are discussed. Keywords: teachers’ instructional practice, classroom management, innovation, self-efficacy.
Keywords: teachers’ instructional practice; classroom management; innovation; self-efficacy; Type of access: Open Access; Research Subject Categories::SOCIAL SCIENCES